The Untameable Trotzkopf: Commerce and Canonicity in the Curious Circulation of a Classic of German Children's Literature in the Low Countries and Germany. (3rd May 2020) - Feldmann, Theresia
ABSTRACT: This paper investigates the multidirectional circulation of the Trotzkopf series in the Low Countries and Germany. Emmy von Rhoden's Der Trotzkopf (1885), a classic of German children's literature, and its sequels were almost immediately translated into Dutch. However, Stijfkopje als Grootmoeder (1904) the sequel that completes the series, was written by the Dutch writer Suze la Chapelle-Roobol. Translated into German it was treated as an original part of the official series. Through a functional analysis of the text based on criteria formulated by Aleida Assmann in her essay on written folklore, this article tries to uncover the transnational mechanisms of canonization, circulation, and reception behind the series. It reveals that consecration and circulation were largely reception- and commerce-driven and not initiated by critics and literary institutions as is often the case for canonical works of adult fiction, confirming earlier findings in research on the canonization of children's literature.